Novi telemedicinski sistem v slovenski transfuzijski službi - Breskvar, Marko (Informatica Medica Slovenica, 2012)
The Slovenian blood transfusion service is using a national telemedicine system since 2005, providing remote work capabilities to specialists of transfusion medicine. Telemedicine allows for substituting on-premises specialists with a remote on-duty specialist, and as such provides a comparable level of service for all patients, with considerable savings in thenational health budget as an added bonus. The current system, planned only for teleconsultations, outgrew its primary scope with the reorganization of Slovenian transfusion service, which increased the number of B2B services. Rapid growth of the delivered services outpaced the current IT infrastructure,thus demanding the ongoing development of a new system.
Keywords: Blood Transfusion; Computer Communication Networks; Health Services; Krvna transfuzija; Organization And Administration; Računalniške mreže; Telemedicina; Telemedicine; Zdravstvene službe